Dualisme Kompetensi Permohonan Pengangkatan Anak Bagi yang Beragama Islam - Antonius Sidik Maryono (Departemen Hukum Perdata, 2018)
The child adoption application for Moslem applicants and Moslem adopted children prospective are authorized by the State Court and the Religion Court in practice, thus this matter causes the competency dualism in accepting, examining, and assigning that child adoption application. In the Mojokerto State Court Decision No.04/Pdt P/2012//PN Mkt, the Purwokerto Religion Court Decision No.130/Pdt P/2014/PA Pwt, the Purwokerto State Court Decision No./Pdt P/2015/PN Pwt. And the Wantanpone Religion Court Decision No.0078/Pdt P/2011/PA Wtp., those fourth courts state that they are authorized to accept, examine and assign the adoption of children. According to the research, by yuridis normative approach result of the child adoption application proposed by Moslem applicants, both in the Religion Court and through the State Court has the authority to accept, examine, grant, and assign the child adoption application, yet with different legal consideration. In the State Court Decision, the judicial legal consideration refers to the common legislation law such as the Child Protection Laws, the Population Administrations Law, the Government Ordinance, and the Supreme Court Circular, however, the Religious Court is based on the Islamic Law compilation. The legal consequences caused by child adoption decision carried out in the state Court, the adopted children have inheritance rights from the adoptive parents, while in the Religious Courts, the adored children do not server ties with the biological parents. Therefore the adopted children do not inherit property from the adoptive parents.